Method to characterize inorganic particulates in lung tissue biopsies using field emission scanning electron microscopy. (2nd September 2018) - Lowers, Heather A.; Breit, G. N.; Strand, M.; Pillers, R. M.; Meeker, G. P.; Todorov, T. I.; Plumlee, G. S.; Wolf, R. E.; Robinson, M.; Parr, J.; Miller, R.; Groshong, S.; et al.
Abstract: Humans accumulate large numbers of inorganic particles in their lungs over a lifetime. Whether this causes or contributes to debilitating disease over a normal lifespan depends on the type and concentration of the particles. We developed and tested a protocol for in situ characterization of the types and distribution of inorganic particles in biopsied lung tissue from three human groups using field emission scanning electron microscopy (FE-SEM) combined with energy dispersive spectroscopy (EDS). Many distinct particle types were recognized among the 13 000 particles analyzed. Silica, feldspars, clays, titanium dioxides, iron oxides and phosphates were the most common constituents in all samples. Particles were classified into three general groups: endogenous, which form naturally in the body; exogenic particles, natural earth materials; and anthropogenic particles, attributed to industrial sources. These in situ results were compared with those using conventional sodium hypochlorite tissue digestion and particle filtration. With the exception of clays and phosphates, the relative abundances of most common particle types were similar in both approaches. Nonetheless, the digestion/filtration method was determined to alter the texture and relative abundances of some particle types. SEM/EDS analysis of digestion filters could be automated in contrast to the more time intensive in situ analyses.